David & Alice Van Buuren : Prix de sculpture monumentale. (Ukkel : Museum David & Alice Van Buuren, 1994)
Leroy, Christian ; Cassamajor, Tristan ; Eijberg, André ; Gangolf, Serge ; Jezierski, Fonny ; Joiris, Nathalie ; Perdieus, Paul ; Rocour, Lambert ; de Schaetzen, Christine ; Verhellen, Tjerrie ; Vokaer, Robin
David & Alice Van Buuren : Prix de sculpture monumentale / Monumentale beeldhouwprijs, Museum David & Alice Van Buuren, Ukkel, 1994
boek